Genetic diversity and population structure of Alternaria species from tomato and potato in North Carolina and Wisconsin - Tika B. Adhikari (Nature Portfolio, 2021)
Abstract Early blight (EB) caused by Alternaria linariae or Alternaria solani and leaf blight (LB) caused by A. alternata are economically important diseases of tomato and potato. Little is known about the genetic diversity and population structure of these pathogens in the United States. A total of 214 isolates of A. alternata (n = 61), A. linariae (n = 96), and A. solani (n = 57) were collected from tomato and potato in North Carolina and Wisconsin and grouped into populations based on geographic locations and tomato varieties. We exploited 220 single nucleotide polymorphisms derived from DNA sequences of 10 microsatellite loci to analyse the population genetic structure between species and between populations within species and infer the mode of reproduction. High genetic variation and genotypic diversity were observed in all the populations analysed. The null hypothesis of the clonality test based on the index of association $$\left( {\overline{r}_{d} } \right)$$ r ¯ d was rejected, and equal frequencies of mating types under random mating were detected in some studied populations of Alternaria spp., suggesting that recombination can play an important role in the evolution of these pathogens. Most genetic differences were found between species, and the results showed three distinct genetic clusters corresponding to the three Alternaria spp. We found no evidence for clustering of geographic location populations or tomato variety populations. Analyses of molecular variance revealed high (> 85%) genetic variation within individuals in a population, confirming a lack of population subdivision within species. Alternaria linariae populations harboured more multilocus genotypes (MLGs) than A. alternata and A. solani populations and shared the same MLG between populations within a species, which was suggestive of gene flow and population expansion. Although both A. linariae and A. solani can cause EB on tomatoes and potatoes, these two species are genetically differentiated. Our results provide new insights into the evolution and structure of Alternaria spp. and can lead to new directions in optimizing management strategies to mitigate the impact of these pathogens on tomato and potato production in North Carolina and Wisconsin.